THE EFFECT OF IMPLEMENTING PERTAMINA SAFETY APPROVAL (PSA) AND SAFETY TRAINING ON WORK SAFETY MEDIATED BY SAFETY CULTURE ON PT PERTAMINA INTERNATIONAL SHIPPING SHIP FLEET - Siregar, Diwan Adfi; Wahyu syafitra, Budi; Febriansyah, Gandha; Nuri Hakim, Ade (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2024)
Pertamina Safety Approval (PSA)is a document that is shown when the ship has met the standards and criteria of the vetting inspection results. The aim of the research is to determine the effect of implementing Pertamina Safety Approval (PSA) and safety training on work safety mediated by safety culture on PT's fleet of ships. Pertamina International Shipping. Method presearch with an explanatory quantitative approach. The number of samples is 90respondents who have a PSA and are on board in 2022. The analysis tools used are SPSS and SEMPLS. The research results show that there is a direct and indirect influence between the implementation of Pertamina Safety Approval (PSA) and safety training on work safety mediated by safety culture on PT's fleet of ships. Pertamina International Shipping.